Crystallization Control of Anionic Thiacalixarenes on Silicon Surface Coated with Cationic Poly(ethyleneimine) - Anna A. Botnar (20146291) (2024)
Surface modification of solid substrates with organic molecules and polyelectrolytes is a promising strategy toward advanced soft materials due to the control of molecular arrangement and supramolecular organization; however, understanding the nature of interactions within the assembly is challenging. Here a facile approach to the control of the architecture of calixarene macrocycles on soft surfaces is presented through the interplay of weak interactions involving a solid silicon substrate, a cationic polyelectrolyte layer, and anionic sulfonatothiacalix[4]arene (STCA). Topological analysis of atomic force microscopy (AFM) images of STCA on silicon, as well as silicon wafers modified with neutral polyethylenimine (PEI) and cationic PEI-H+, indicates different surface morphology and assembly behavior of STCA on such substrates. Drop-casting a calixarene solution onto silicon induces the formation of chaotically oriented needle crystals. When there is globular PEI, a nucleation point for the STCA crystals is formed on the polyelectrolyte surface, which grows into rosette structures. In contrast, protonated PEI with a chain-like structure alters the self-organization of STCA on silicon surfaces, leading to a dense uniform fiber-like network. Density functional theory modeling of the system components' self-assembly reveals thermodynamically favorable face-to-face antiparallel aggregation of STCA monomers and contribution of H-bonding into PEI(PEI-H+)–STCA and Si–STCA association.